The Implementation Of Inquiry-Based Learning In Teaching Reading At The First Year Of MTs Al Islam Mranggen In 2014/2015 Academic Year - Anitasari, Wulan Septi, Aryati Prasetyarini, S.Pd, M.Pd, NurHidayat, M.Pd (2016)
This research aims at describing the implementation of Inquiry-based Learning in teaching reading and the problems faced by the teacher in implementing the method at the first year of MTs Al-Islam Mranggen. The writer gets the data of this research from event, informant and document.The methods of collecting data are observation, interview, and documentation. This research uses descriptive qualitative. The steps for analysis data are data reduction, data display also conclusion and verification.The results of the analysis showthat: 1) Inquiry-based Learning was conducted in teaching reading at the first year of MTs Al-Islam Mranggen following three stages namely, exploration, elaboration, and confirmation. The implementation of method was less complete because the activities in standard process were not implemented in teaching reading fully. 2) the problem faced by the teacher in implementing the method were lack of knowledge about Inquiry-based Learning on how to implement the method, class management, limited time, lack of material and lack of teaching media. The solutions for the problems are: a) the headmaster should give evaluation to the teacher in using method and media in teaching learning process and give chance for the teacher to follow the seminar, teaching training and workshop. b) the teacher should have knowledge before they implement this method in the class, so in teaching learning process there will be no misunderstanding.